Prevalence of and risk factors for chlamydia in female outpatients with genital tract infections: a nationwide multi-center, cross-sectional study in China - Ting Li; Zhaohui Liu; Dai Zhang; Qinping Liao; Shangrong Fan; Min Hao; Ying Hong; Xiufeng Huang; Huilan Wang; Zhengai Xiong; Hong Xu; Fengxia Xue; et al. (Frontiers Media S.A., 2023)
IntroductionChlamydia trachomatis is the etiological agent of the commonest sexually transmitted bacterial infection. This study aimed to examine the prevalence of genital chlamydia and associated risk factors in Chinese female outpatients with genital tract infections.MethodsA prospective, multicenter epidemiological study of genital chlamydia prevalence in 3008 patients with genital tract infections in 13 hospitals in 12 provinces of China was performed between May 2017 and November 2018. Vaginal secretion specimens were collected for the clinical diagnosis of vaginitis, whereas cervical secretion specimens were tested for Chlamydia trachomatis and Neisseria gonorrhoeae. All patients participated in a one-on-one cross-sectional questionnaire interview. ResultsTotally 2,908 participants were included. The prevalence rates of chlamydia and gonococcal infections in women with genital tract infections were 6.33% (184/2908) and 0.01% (20/2908), respectively. Multivariate analysis showed high risk factors for chlamydia were premarital sex behavior, first sexual intercourse before the age of 20 and bacterial vaginosis.DiscussionGiven that most chlamydia cases are asymptomatic and no vaccine is currently available, chlamydia prevention strategies should include behavioral interventions as well as early screening programs to identify and treat individuals with genital tract infections, especially those with the above identified risk factors.